Living safely with epilepsy: a key learning review. Issue 4 (19th September 2020) - Bertinat, Andrés; Kerr, Mike; Cramer, Joyce A.; Braga, Patricia
Abstract: This review focusses on counselling to reduce the risks of seizures in epilepsy patients. Risk reduction, whilst maximising the independence of persons with epilepsy, is a core element of epilepsy practice. The importance of the issue is reflected by the inclusion of risk assessment and reduction in the recent International League Against Epilepsy Curriculum for epileptology. This article addresses the key elements of epilepsy risk and provides practical guidance for counselling and risk reduction. A review of key publications was performed focusing on: (1) the risk of injury associated with seizures; (2) safety issues related to seizures and lifestyle; (3) SUDEP risk and avoidance; and (4) assessing individual risks. Risk is common in epilepsy and is multifactorial. Clinicians should be aware of the risk factors associated with different epilepsy features, such as seizure type, as well as those related to lifestyle and common indoor and outdoor activities. In addition, transcultural differences should be considered in risk assessment and counselling, e.g. regarding SUDEP or even driving, for which regulations vary across nations. Assessment of individual risk is evolving through a better understanding of risk factors and methodologies which can improve communication and empower patients to help identify and manage their individual risks.